2015
DOI: 10.1186/s40345-014-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Switch to mania after ayahuasca consumption in a man with bipolar disorder: a case report

Abstract: BackgroundThere is an increasing use of ayahuasca for recreational purposes. Furthermore, there is a growing evidence for the antidepressant properties of its components. However, there are no reports on the effects of this substance in the psychiatric setting. Harmaline, one of the main components of ayahuasca, is a selective and reversible MAO-A inhibitor and a serotonin reuptake inhibitor.Case reportWe present the case of a man with bipolar disorder who had a manic episode after an ayahuasca consumption rit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 12 publications
(12 reference statements)
0
34
0
3
Order By: Relevance
“…Ayahuasca may be contraindicated for bipolar disorders patients, since a recent case report described a man with bipolar disorder that developed a manic episode after ayahuasca consumption. 12 Increased blood perfusion in the subgenual area, nucleus accumbens, and insula were observed after ayahuasca intake. Hypoactivation of these brain regions is usually associated with depression, while increased activation is usually associated with antidepressive effects.…”
Section: Discussionmentioning
confidence: 98%
“…Ayahuasca may be contraindicated for bipolar disorders patients, since a recent case report described a man with bipolar disorder that developed a manic episode after ayahuasca consumption. 12 Increased blood perfusion in the subgenual area, nucleus accumbens, and insula were observed after ayahuasca intake. Hypoactivation of these brain regions is usually associated with depression, while increased activation is usually associated with antidepressive effects.…”
Section: Discussionmentioning
confidence: 98%
“…[94] also suggested that recreational DMT use could be a contributor to psychosis. Another case report discussed a man with preexisting bipolar disorder who had a manic episode following ayahuasca consumption [95].…”
Section: Physiologic Effects Safety and Adverse Effectsmentioning
confidence: 99%
“…Another report associated an individual with polar disorders, that presented a manic episode after in a 4-day ingested ayahuasca, without any caution [155]. Also, intoxication by β-carboline alkaloids in a P. harmala seeds infusion was reported [156].…”
Section: Cases Of Intoxication Associated With the Ingestion Of Ayahumentioning
confidence: 99%